Tryptic peptide analysis of gag and gag-pol gene products of Rauscher murine leukemia virus. - Kopchick, J J (1979)
[3H]tyrosine-labeled viral precursor polyproteins and known mature viral proteins derived from the Rauscher murine leukemia virus gag and pol genes were examined by two-dimensional tryptic peptide mapping. Pr200gag-pol was found to contain peptide sequences of the viral core proteins p30, p15, p12, and p10, as well as peptide sequences found in the cell-associated reverse transcriptase. Intermediate reverse transcriptase precursor Pr125pol lacked peptide sequences of the four-core proteins but contained reverse transcriptase-specific tryptic peptides plus two additional tyrosine-containing tryptic peptides not related to gag or pol gene products. Methionine-containing tryptic peptide analysis also suggested the presence of additional protein material in Pr125pol (Kopchick et al., Proc. Natl. Acad. Sci. U.S.A. 75:2016-2020, 1978). Pr200gag-pol, although containing both viral core and reverse transcriptase-assoicated methionine and tyrosine tryptic peptides, also contained additional tryptic peptides. Thes are of two classes: (i) tryptic peptides associated with the Pr125pol but not Pr80pol and (ii) tryptic peptides not found in Pr125pol or in any known viral protein. One interpretation of these results is that Pr200gag-pol contains additional gene products aside from the gag and pol genes. Pr80gag and Pr65gag peptide maps were also examined and found to have sequences of all four core proteins. Pr65gag was found to contain two p30 tyrosine tryptic peptides that were absent in Pr80gag, suggesting that Pr80gag may not be the precursor to Pr65gag. Pr80gag, as expected from its larger size, also contained tryptic peptides not found in Pr65gag. Two of these additional Pr80gag tryptic peptides were found in Pr80pol as well but not in any of the viral core proteins, suggesting that Pr80gag and Pr80pol may have overlapping peptide sequences. Consistent with this finding is the conclusion that Pr80gag terminates within the pol gene. A model that describes the relationship of these recent findings to viral gene products is presented.